BmNPV p35 Reduces the Accumulation of Virus-Derived siRNAs and Hinders the Function of siRNAs to Facilitate Viral Infection - Zhao, Shudi; Chen, Guanping; Kong, Xiangshuo; Chen, Nan; Wu, Xiaofeng (Frontiers in Immunology, 2022)
Antiviral immunity involves various mechanisms and responses, including RNA interference (RNAi) pathway. During the long-term coevolution, viruses have gained the ability to evade this defense by encoding viral suppressors of RNAi (VSRs). It was reported that p35 of baculovirus can inhibit cellular small interference RNA (siRNA) pathway, however, the molecular mechanisms underlying p35 as a VSR remain largely unclear. Here, we showed that p35 of Bombyx mori nucleopolyhedrovirus (BmNPV) reduces the accumulation of virus-derived siRNAs (vsiRNAs) mapped to a particular region in viral genome, leading to an increased expression of the essential genes in this region, and revealed that p35 disrupts the function of siRNAs by preventing them from loading into Argonaute-2 (Ago2). This repressive effect on cellular siRNA pathway enhances the replication of BmNPV. Thus, our findings illustrate for the first time the inhibitory mechanism of a baculovirus VSR, and how this effect influences viral infection.